Acoustic Properties of Autoclaved Aerated Concrete (AAC) based on Gypsum-Ceramic Waste (GCW) - Yusrianto, Efil; Marsi, Noraini; Kassim, Noraniah; Abdul Manaf, Izzati; Hakim Shariff, Hafizuddin (International Journal of Integrated Engineering, 2022)
Noise pollution and municipal solid waste (MSW) are two ongoing issues for inhabitants of urban due to the growth development. We need to manage of MSW such as gypsum and ceramic waste properly to solve environment and acoustic issues. To our knowledge, the gypsum and ceramic waste (GCW) are rich in silica and calcium oxide and have been recognized and approved to have a good building material such as lightweight concrete and also have a good sound insulation material. Meanwhile, autoclaved aerated concrete (AAC) is one of the lightweight concrete family members and the major chemical composition is silica, calcium oxide and small amount of iron and aluminum. Due to the similarities of major chemical composition between AAC and GCW, it was interesting to study the acoustic properties of AAC based on GCW as an alternative natural source for partial fine aggregate replacement. The objective of this work was to determine the performance of the acoustic properties of AAC based on GCW in addition to reduce the negative effect of GCW on the environment. The AAC with different composition of GCW (5%, 10%, and 15%wt) has been prepared according to ASTM C1693-09. The compressive strength was in range of 5.08 to 7.10MPa. The sound absorption of all samples has been carried out at range of 350Hz to 2000Hz according to ASTM E1050. The results found that AAC-GCW performed well in terms of sound absorbance but in different frequency range. The sound absorption coefficient was around 0.77 to 0.88 at 1050 – 1350Hz. Our results indicated the GCW can use as an alternative natural source for partial fine aggregate replacement on AAC and has improved the acoustic properties of AAC samples. The best sound absorption coefficient was showed by AAC with 10% wt of GCW i.e 0.88. Generally, AAC-GCW samples have higher sound absorbance coefficient compare to previous studies and suitable for wall application such as partition walls, party walls, and especially for sound insulation material.